Soy product consumption and the risk of major depressive disorder in older adults: Evidence from a cohort study - Zhang, Tao; Jiang, Guojun; Li, Fudong; Gu, Xue; Zhai, Yujia; Xu, Le; Wu, Mengna; Shen, Hongwei; Lin, Junfen (Frontiers in Psychiatry, 2022)
Background: To explore the association between soy products consumption and risk of depression in community. Methods: In 2014, a total of 10901 older people were recruited from Zhejiang province, China, and completed food frequency interview. Participants were followed up in the next six years, and depression was assessed at each visit. Mixed effects models were performed to analyze the association by multivariate adjustments for potential confounders. Results: Over four-fifths of the eligible participants took soy food at least one day per week. Mixed effects model has shown the adjusted odds ratios (95% confidence interval) of high frequency consumers (4-7 days per week) were 0.46 (0.39-0.54) for depression with a cut-off score of 5, compared with non-consumers. Conclusions: More frequent soy products consumption was associated with lower risk of depression.